PARENT’S CARE PATTERN TOWARD LEVEL OF CHILD’S CREATIVITY - Yusiana, Maria Anita; Teviana, Fenia (Jurnal Penelitian STIKES Kediri, 2012)
Creativity is a dimension of child ability in developing science, technological, and artistic. Appropriate parentâ€™s care pattern will optimize childâ€™s creativity. The purpose of this research was to analyze correlation between parentâ€™s care patterns and child creativityâ€™s level at Dharma Wanita Kindergarten Kelurahan Bangsal Kediri. The researchâ€™s design was correlation analytic. The populations were all children and parents at Dharma Wanita Kindergarten Kelurahan Bangsal Kediri. Using Total Sampling, it was obtained 132 respondents who fulfilled inclusion criteria. The independent variable was parentâ€™s care patterns while the dependent variable was child creativityâ€™s level. The data were collected by the structure interview and questioners. Those were analyzed using the statistical test of lambda with level of significance Ï = 0.05. The result showed significance Ï = 0,028, it meant Ho refused, so that there was correlation between the level of childâ€™s creativity and parentâ€™s care pattern at Dharma Wanita Kindergarten Kelurahan Bangsal Kota Kediri. Authoritative parentâ€™s care pattern optimizes child creativityâ€™s level. Further studies are suggested to analyze the other factors that influence the level of child creativityâ€™s level which is not yet studied in the recent research. Those are age, the parentâ€™s education, the availability of facility, and time spent.